Accessibility and use of records in educational policy-making in selected ministries of education in South-west, Nigeria (2017)
Purpose: This study investigated accessibility and use of records for educational policy making by senior civil servants in selected state ministries of education in South-West, Nigeria. Design/Methodology/Approach: The descriptive survey research design was adopted for the study. The population of the study consisted of 1,205 senior civil servants in Ministries of Education in South-west, Nigeria out of which a sample size of 241 respondents was derived. A questionnaire was used for data collection. The data collected through the questionnaire were complemented with interview conducted with a Director, Deputy Director and a senior officer in Lagos State, Ogun State and Osun State by the researchers. The data collected with the questionnaire were analyzed using descriptive statistics, Pearson correlation and regression analysis while content analysis of the recorded interviews was made. Findings: The study revealed that accessibility and use of records significantly predicted educational policy making (R2=.055, F (2,240) = 6.898, p<-05) with 5.5% explanation of the variability of the dependent variable. It also revealed that records needed for educational policy making include academic records of students, annual reports from schools, inspection reports and yearly approved estimates. It identified politics, power supply and bureaucratic system as the major constraints to timely accessibility and use of records. Implication: The study has implication for the management of records in the public sector. Suggested solutions to the challenges in the accessibility and use of records include putting in place mechanisms to remove or reduce the constraints to timely accessibility and use of records for educational policy making, setting standard for formulating, implementing and sustaining educational policies made and considering continuity in the established policies. Originality/Value: the originality of this study lies in the finding that accessibility and use of records significantly predicted educational policy making.